PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. J&T TEKNOLOGI EXPRESS – SDP PONDOK AREN - Hadyati Harras; Devi Fitria Wilandari; Sinta Sulistiani (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The purpose of this study was to determine the effect of leadership on employee productivity at PT J&T Technology Express-SDP Pondok Aren. To find out the Effect of Work Discipline on Employee Productivity at PT J&T Technology Express-SDP Pondok Aren, and to find out the effect of Leadership and Work Discipline on Employee Work Productivity at PT J&T Technology Express-SDP Pondok Aren. The method used is Quantitative Associative method. The sampling technique used is saturated sample method with a sample of 112 employees. Methods of data analysis using simple linear regression test, multiple linear regression, correlation coefficient, determination coefficient, partial t test and F test. The results of this study indicate that partially there is a positive and significant influence between Leadership on Employee Work Productivity at PT J&T Teknologi Express-SDP Pondok Aren, this can be proven from the simple linear regression equation Y = 26.515 + 0.326X1, The correlation value is 0.413. The coefficient of determination is 17%, and the value of tcount3,655 > ttable1.99773 with a significance of 0.001 <0.05. Partially there is a positive and significant influence between Work Discipline on Employee Work Productivity at PT J&T Technology Express-SDP Pondok Aren, this can be proven from the simple linear regression equation Y = 17.441 +0.389X2, The correlation value is 0.573. The coefficient of determination is 32.9%, and the value of tcount5,640 > ttable 1.99773 with a significance of 0.000 <0.05. Simultaneously there is a positive and significant influence between Leadership and Work Discipline on Employee Work Productivity at PT J&T Technology Express-SDP Pondok Aren, this can be proven from the multiple linear regression equation Y = 13.105 + 0.197X1 +0,332X2. The coefficient of determination is 39.2%, as well as the F valuecount 19,917 > Ftable3.14 with a significant level of 0.000 <0.05.